ARAHAN PEMANFAATAN LAHAN PERTANIAN TANAMAN SEMUSIM TERHADAP RISIKO BENCANA LONGSORLAHAN DI WILAYAH URBANISASI PERDESAAN LAHAN ATAS GUNUNGAPI - Nugroho Hari Purnomo (Metafora: Education, Social Sciences and Humanities Journal, 2020)
Land use is an important variable in determining the incidence of landslide. Whereas the use of agricultural land crops are vital assets socio-economic life of small farmers in the rural areas on land in the area of complex quarter Arjuno volcano in East Java. This makes the direction of conservation of farmland crops indispensable as an effort to suppress landslide disaster risk. This study aims to determine the direction of agricultural land use crops to reduce disaster risk landslide. Survey method based Disaster Risk Level Map Landslide the basis for this study. Referrals are based on landform conservation, land use, and spatial variation landslide disaster risk with regard to geographical location. Analysis is conducted visually descriptive and to the table. The results show that the direction of agricultural land use crops against landslide disaster risk level should pay attention landform, slope, and rainfall. Urbnisasi region rural farming communities change of socio-economic and cultural aspects due to the ease of access to the interaction with urban areas. This has an impact on the orientation of their lives are no longer entirely dependent on land resources so often ignored aspects of land conservation.